2009
DOI: 10.1111/j.1365-2230.2008.03164.x
|View full text |Cite
|
Sign up to set email alerts
|

CutaneousFusarium solaniinfection in childhood acute lymphoblastic leukaemia

Abstract: Cutaneous involvement is often an initial presentation of infection with Fusarium species, which occurs more commonly in immunocompromised hosts and may be either localized or widespread. Skin lesions typically appear as red or grey macules, which may develop central ulceration and black eschar. Secondary dissemination to extracutaneous organs may occur in immunocompromised hosts, especially those with prolonged and severe neutropenia. We describe a case of widespread cutaneous involvement after infection with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 8 publications
0
37
1
Order By: Relevance
“…Other published cases have revealed the priority of using amphotericin B as the sole therapy or in combination with voriconazole in treatment of fusariosis. [28][29][30][31][32][33][34][35][36][37][38][39][40][41] These results are in contrast to the proposed antagonism that may exist between amphotericin B and triazole antifungal agents. 29 This antagonism has been proposed due to the fact that the synthesis of ergosterol, which is the target for amphotericin B, is inhibited by azoles.…”
Section: Clinical Datamentioning
confidence: 60%
“…Other published cases have revealed the priority of using amphotericin B as the sole therapy or in combination with voriconazole in treatment of fusariosis. [28][29][30][31][32][33][34][35][36][37][38][39][40][41] These results are in contrast to the proposed antagonism that may exist between amphotericin B and triazole antifungal agents. 29 This antagonism has been proposed due to the fact that the synthesis of ergosterol, which is the target for amphotericin B, is inhibited by azoles.…”
Section: Clinical Datamentioning
confidence: 60%
“…are considered the second most-common mold as cause of opportunistic infection in these patients, being Aspergillus spp. the first ones (Bodey et al 2002; Cooke et al 2009). Fusarium spp.…”
Section: Discussionmentioning
confidence: 99%
“…32 Penetrating trauma remains the major cause of primary cutaneous zygomycosis (Table 2). [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Other causes reported include elasticized bandages and wound dressings, 55 burns, 56 motor vehicle collision, 57 intravenous access, 58 and dog bite. 59 Our case report of primary cutaneous mucormycosis after a cat bite is a rare finding.…”
Section: Discussionmentioning
confidence: 99%
“…66 The higher overall mortality rate of 29.4% seen in the review of the literature was observed more frequently in patients with neutropenia (60.0%) and without surgical intervention (73.3%), and the survival rate was higher (35.3%) for cases utilizing both antifungal and surgical interventions. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] The antifungal agent with the highest survival rate was amphotericin B and its formulations (58.8%). [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation